2015
DOI: 10.1371/journal.pone.0141594
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Leaving Hospital against Medical Advice among People Who Use Illicit Drugs in Vancouver, Canada

Abstract: BackgroundLeaving hospital against medical advice (AMA) is common among people who use illicit drugs (PWUD) and is associated with severe health-related harms and costs. However, little is known about the prevalence of and factors associated with leaving AMA among PWUD.MethodsData were collected through two Canadian prospective cohort studies involving PWUD between September 2005 and July 2011 and linked to a hospital admission/discharge database. Bivariable and multivariable generalized estimating equations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
58
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 36 publications
6
58
0
3
Order By: Relevance
“…AMA discharges are associated with higher mortality rates, more frequent readmissions, and greater likelihood of future AMA discharges 5 . Reasons for the AMA discharge may include the desire to use drugs, opioid withdrawal, poor pain control, poor communication with staff, or feeling stigmatized 6,7 . In a study of 488 people who used illicit drugs with at least one prior hospitalization, almost half (43.4%) reported experiencing at least one AMA discharge 7 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…AMA discharges are associated with higher mortality rates, more frequent readmissions, and greater likelihood of future AMA discharges 5 . Reasons for the AMA discharge may include the desire to use drugs, opioid withdrawal, poor pain control, poor communication with staff, or feeling stigmatized 6,7 . In a study of 488 people who used illicit drugs with at least one prior hospitalization, almost half (43.4%) reported experiencing at least one AMA discharge 7 …”
Section: Introductionmentioning
confidence: 99%
“…5 Reasons for the AMA discharge may include the desire to use drugs, opioid withdrawal, poor pain control, poor communication with staff, or feeling stigmatized. 6,7 In a study of 488 people who used illicit drugs with at least one prior hospitalization, almost half (43.4%) reported experiencing at least one AMA discharge. 7 Prior studies have identified a number of factors that reduce AMA discharges among PWID, including the use of methadone during and prior to the hospitalization and the implementation of an addiction consultation service.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with conventionally discharged patients, AMA patients are younger, more likely to be male, and more likely a marginalized ethnic or racial minority. [10][11][12][13][14] Patients with mental illnesses and addiction issues are overrepresented in AMA discharges, and complicated capacity assessments and limited resources may strain providers. 7,8,15,16 Studies have repeatedly shown higher rates of readmission and mortality for AMA patients than for conventionally discharged patients.…”
mentioning
confidence: 99%
“…[45][46][47][48] Qualitative research and one systematic review found that opioid withdrawal, inadequate pain management, younger age, daily heroin injection and unstable employment were factors contributing to discharges against medical advice among patients with substance use disorders. 29,49,50 Available evidence suggests that opioid agonist therapy, when paired with referral to outpatient addiction services, may reduce discharge against medical advice and increase engagement in postdischarge addiction treatment. [51][52][53][54][55] One observational study of in patients with opioid use disorder showed that initiation of methadone during the hospital stay, coupled with linkage to an outpatient addiction program, led to a high rate (82%) of postdischarge follow-up.…”
Section: Is There Benefit To Inpatient Initiation Of Opioid Agonist Tmentioning
confidence: 99%